Characterization of Soil Properties Under Continuous Irrigation Practice - Bala YAHAYA; Mukhtar N. YAHYA (FUDMA Journal of Engineering and Technology, 2025)
Continuous irrigation, though essential for agricultural productivity in semi-arid regions, can significantly alter soil physical and chemical properties over time. In Kano State, Nigeria, there is limited recent data on how continuous irrigation affects different soil textures such as sandy loam and loamy soils. This study aims to assess the impact of continuous irrigation on the physical and chemical properties of soils under Watari Irrigation Scheme, with a focus on identifying implications for sustainable soil management. Soil samples were collected from irrigated and adjacent non-irrigated (control) fields of sandy loam and loam textures at two depths:0-30cm and 30-60cm, replicated three times. A total of 24 samples were analyzed for physical properties (moisture content, bulk density, hydraulic conductivity), and chemical properties (organic matter, salinity (EC), Sodium Adsorption Ratio (SAR), Total Dissolved Solids (TDS), Cation Exchange Capacity (CEC), pH (H2O), pH (CaCl2), Sodium (Na+), Calcium (Ca2+), Magnesium (Mg2+), Potassium (K+). Standard laboratory procedures were used, and statistical analysis was performed using SPSS v25 with ANOVA at a 5% significance level. Results showed that the texture-dependent respond to continuous irrigation. Bulk density slightly decreased in irrigated sandy loam (1.48 to 1.46g/cm3) and slightly increased in loam (1.41 to 1.42g/cm3), with a corresponding decrease in porosity. Moisture content was higher in non-irrigated sandy loam (15.67%) also higher in irrigated loam (16.46%). The results of this study indicates that non-irrigated soils retain more moisture but exhibit higher salinity and sodium accumulation particularly in sandy loam, TDS levels reached 262.4mg/l compared to 108.8mg/l in irrigated soil. Loamy soil demonstrated superior moisture retention (16.46%) and lower bulk density (1.41g/cm3), making it more suitable for water-intensive crops. Pearson correlation analysis (-0.67) revealed a negative relationship between bulk density and moisture content, indicating that compacted soils retain less water. This indicates that continuous irrigation may contribute to nutrient leaching and reduce soil fertility over time. Other properties EC, pH, Na+, Ca2+, K+, SAR, and TDS do not show significant variations in the two conditions. The findings show that continuous irrigation reduces soil salinity and enhances nutrient availability, however, it may contribute to compaction in sandy loam soils. These highlight the need for texture-specific soil management. Gypsum application and organic amendments are recommended for sodium-affected soils, while strategic irrigation scheduling is necessary to optimize water use efficiency. These results provide valuable indicators for sustainable irrigation practice and strategies, soil management and crop selection (such as organic amendments and optimized irrigation scheduling, to maintain soil nutrients balance and fertility in Watari irrigation project under semi-arid agricultural systems).